Did Career Development, Organizational Citizenship Behavior and Leadership Reinforce Teachers Performance? Answer From Elementary Schools in Tangerang - Nugroho, Yunianto Agung; Wijaya, Muhamad Rizky; Jainuri; Pramono, Tias; Johan, Muhammad (International Journal of Social and Management Studies, 2022)
This study aims to analyze the relationship of career development, organizational citizenship behavior, and leadership to the Head of elementary school performance. This research method is quantitative with data processing tools using SPSS software. Data was obtained through the distribution of online questionnaires to 212 elementary school teachers in Tangerang who were selected using the simple random sampling method. Based on data analysis, it can be concluded that career development has a positive effect on teacher performance, organizational citizenship behavior has a positive effect on teacher performance, leadership has a positive effect on teacher performance and career development, organizational citizenship behavior and leadership simultaneously have a positive and significant effect on teacher performance.